Role of zinc supplementation in the management of chronic liver diseases: A systematic review and meta-analysis - Diglio, Daniela C.; Fernandes, Sabrina A.; Stein, Jessica; Azeredo-da-Silva, André; de Mattos, Angelo A.; Tovo, Cristiane V. (Annals of hepatology, 2020)
Zinc deficiency has been associated with poor prognosis in chronic liver disease. This systematic review and meta-analysis aimed to evaluate the role of zinc supplementation in the management of chronic liver diseases. We searched MEDLINE, LILACS, EMBASE, and Cochrane CENTRAL databases from inception to August 2018. We included randomized controlled trials evaluating adult patients with chronic liver disease of any etiology receiving zinc supplementation. Studies with other designs or evaluating chronic conditions other than liver disease were excluded. Two reviewers independently screened and extracted data from eligible studies. Study quality was assessed using the Cochrane Collaboration's tool for assessing risk of bias in randomized studies. Of 1315 studies screened, 13 were included. Six assessed chronic hepatitis C treatment, with a relative risk of 0.83 indicating no protective effect of zinc supplementation on the improvement of sustained virological response. Three evaluated response to hepatic encephalopathy treatment, with a relative risk of 0.66 indicating a favorable effect of zinc supplementation on clinical improvement of this condition. Of four studies evaluating the management of cirrhosis, two analyzed the effect of zinc supplementation on serum albumin levels, with no statistical difference between zinc and placebo groups. Clinical trials assessing zinc supplementation in liver diseases do not show benefits in terms of clinical improvement or disease halting. There are possible benefits of zinc supplementation on hepatic encephalopathy, however, this is based on limited evidence. This research question is still open for evaluation in larger, well-designed, clinical trials.